Solid oxide fuel cells (SOFCs) fed with biogas containing hydrogen chloride traces: Impact on direct internal reforming and electrochemical performance. (20th November 2022) - Illathukandy, Biju; Saadabadi, S. Ali; Kuo, Po-Chih; Wasajja, Henry; Lindeboom, Ralph E.F.; Vijay, V.K.; Aravind, P.V.
Highlights: Direct internal reforming (DIR) experiments are performed with simulated biogas and steam addition. Experiments at 850 °C with up to 12 ppm(v) HCl in biogas revealed no significant impact on DIR or cell deterioration. At 800 °C, DIR is very marginally affected, whereas both DIR and cell performance are marginally affected at 750 °C. The HCl level used is at par with the reported level in sewage biogas. Post-test analyses of the SOFC reveals no microstructure changes, chlorine infiltration, or nickel chloride formation. Abstract: This study is particularly aimed at investigating the influence of hydrogen chloride traces in biogas on direct internal reforming in solid oxide fuel cells (SOFCs). The experiments are performed with simulated biogas containing methane to carbon dioxide ratio of 3:2, the usual average proportion in biogas. To the best of our knowledge, there are no reported studies that investigated the effect of hydrogen chloride on direct internal reforming by clearly establishing the effect of reforming with outlet gas composition measurements. The experiments at SOFC operating temperature of 850 °C reveals no negative effect on reforming or cell performance, with 4, 8, and 12 ppm(v) of hydrogen chloride in biogas. At 800 °C, there is no visible performance degradation, but a negligible amount of methane (∼ 1%) is detected in the anode off gas. Both the reforming and electrochemical performance are marginally affected at 750 °C. Further, post-test analyses (FESEM-EDS, XRD) of the used SOFC reveals no damage to the cell at microstructure level or chlorine poisoning. All the experiments are performed in the context of utilizing the biogas generated from sewage treatment plants in an SOFC system. The reported level of chlorine traces in biogas generated from sewage sludge is < 10 ppm(v) and hence the limit set for experiments is at par with this value. Graphical abstract: Image, graphical abstract